KEMAMPUAN TARIF INA CBG’S HEMODIALISA PROGRAMKARTU JAKARTA SEHAT (KJS) MENUTUPI BIAYA RIILNYA - Supriadi, Supriadi (UI Scholars Hub, 2015)
Healthy Jakarta Card ( KJS ) is a Health Insurance program provided by Jakarta Provincial Government through the UP . Jamkesda Jakarta Provincial Health Office to the community in the form of medical assistance to the population of Jakarta , especially for the poor and underprivileged with tiered referral system . KJS use tariff system the price of Indonesia Case Base Groups ( INA - CBG 's ) issued by PT Askes ( Persero ) , This study aims to measure the ability of rates Hemodialysis INA CBG 's to cover the real cost , to take the example of a hospital -type B education in North Jakarta . This study used a descriptive analytical approach . The data used are secondary data from reports in 2013 , which then these data are grouped into groups of direct costs and indirect costs . The data were processed using a computer program spreed sheet . The results of this study showed that the rate of CBG 's INA Hemodialysis Program KJS still able to cover the real costs of action Hemodialysis , Hemodialysis where the real cost of only 89.6 % of the fare . Suggested make clinical pathways for each health service that can be incurred cost efficiency .